Counterinsurgency Scorecard Afghanistan in Early 2011 Relative to the Insurgencies of the Past 30 Years - Paul, Christopher (RAND Corporation, 2011)
A core finding of previous RAND research on 30 years of insurgencies worldwide was that a conflict's overall score on a scorecard of 15 equally weighted good and 12 equally weighted bad counterinsurgency factors and practices perfectly predicted the ultimate outcome. Using the scorecard approach and an expert elicitation (Delphi) exercise, a RAND project sought to extend the findings to the case of Afghanistan in early 2011.